\(a, b, c\) ক্রমিক সমানুপাতী হলে, প্রমাণ করো যে, \( \cfrac{1}{b}=\cfrac{1}{b-a}+\cfrac{1}{b-c}\)
Madhyamik 2024
\(a, b, c\) ক্রমিক সমানুপাতী হলে \(\cfrac{a}{b}=\cfrac{b}{c}\)
ধরি, \(\cfrac{a}{b}=\cfrac{b}{c}=k [k\ne 0]\)
\(\therefore a=bk=ck^2,\) এবং \(b=ck\)
বামপক্ষ=\(\cfrac{1}{b}\)
\(=\cfrac{1}{ck}\)
ডানপক্ষ \(=\cfrac{1}{b-a}+\cfrac{1}{b-c}\)
\(=\cfrac{1}{ck-ck^2}+\cfrac{1}{ck-c}\)
\(=\cfrac{1}{ck(1-k)}+\cfrac{1}{c(k-1)}\)
\(=\cfrac{1}{ck(1-k)}-\cfrac{1}{c(1-k)}\)
\(=\cfrac{1-k}{ck(1-k)}\)
\(=\cfrac{1}{ck}\)
\(\therefore\) বামপক্ষ = ডানপক্ষ (প্রমাণিত)